2019
DOI: 10.1038/s41586-019-1244-x
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term ex vivo haematopoietic-stem-cell expansion allows nonconditioned transplantation

Abstract: Multipotent self-renewing hematopoietic stem cells (HSCs) regenerate the adult blood system following transplantation 1 , a curative therapy for numerous diseases such as immunodeficiencies and leukemias 2 . While significant effort has been applied to identify HSC maintenance factors through characterization of the in vivo bone marrow (BM) HSC Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subject always to the full Conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
347
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 308 publications
(355 citation statements)
references
References 29 publications
8
347
0
Order By: Relevance
“…A recent paper reported the 899-fold in vitro expansion of mouse HSCs over the course of one month using cytokine supplementation and polyvinyl alcohol in the medium [79]. To date, the earliest HSCs that have been found to yield long-term, serial, multilineage engraftment in irradiated adult mice arise from the AGM on or around embryonic day 10.5 via EHT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper reported the 899-fold in vitro expansion of mouse HSCs over the course of one month using cytokine supplementation and polyvinyl alcohol in the medium [79]. To date, the earliest HSCs that have been found to yield long-term, serial, multilineage engraftment in irradiated adult mice arise from the AGM on or around embryonic day 10.5 via EHT.…”
Section: Discussionmentioning
confidence: 99%
“…Whether HSCs can be expanded ex vivo remains a question. A recent paper reported the 899-fold in vitro expansion of mouse HSCs over the course of one month using cytokine supplementation and polyvinyl alcohol in the medium [79]. Human HSCs, however, were only shown to expand reliably for 7 days following the same method.…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier stage CIRM awards have explored endogenous paracrine factors that might also be exploited to expand HSPCs in vivo or in vitro, such as pleiotrophin and dickkopf‐1 . Most recently, a CIRM funded exploratory study identified novel culture conditions permitting 236‐899‐fold expansion of highly engraftable, functional murine HSCs in only 30 days, and is currently attempting to replicate this phenomenon in a human HSC culture system (Table ). Although these endeavors are encouraging, each approach affects one or more different subpopulations of blood progenitors and the long‐term engraftability and clinical utility of expanded cells remains unknown.…”
Section: Limited Availability Of Hscs: Improving Donor Cell Sourcesmentioning
confidence: 99%
“…Due to their ability to repopulate the entire hematopoietic system upon transplantation in both mice and humans, HSCs represent the currently established standard for stem cell therapy. To this end, several studies exist that employ different methods to expand these cells ex vivo or generate them de novo [10][11][12][13]. To this end, several studies exist that employ different methods to expand these cells ex vivo or generate them de novo [10][11][12][13].…”
mentioning
confidence: 99%
“…The source material required for these applications, however, remains in limited supply because HSCs notoriously die or differentiate ex vivo [9]. To this end, several studies exist that employ different methods to expand these cells ex vivo or generate them de novo [10][11][12][13]. This issue hinders their use for a multitude of in vitro applications, such as drug testing platforms and disease modeling systems.…”
mentioning
confidence: 99%